Profil senyawa metabolit sekunder dari fraksi n-heksana dan etil asetat daun cengkeh (Syzygium aromaticum L.) menggunakan LC-HRMS - Rezky Yanuarty; Siti Nurhaliza; Halik Alamsyah; Joni Tandi; Muthmainah Tuldjanah; Ayu Wulandari; Kevin Maengko; Recky Patala (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The diversity of plants available in nature, the majority have the potential as a source of traditional medicine due to the presence of secondary metabolites in various parts of the plant, especially the leaves. The object of the study was clove leaves (Syzygium aromaticum L.), a plant species abundant in secondary metabolites including alkaloids, flavonoids, tannins, saponins, and steroids/triterpenoids. This research aims to compare the profile of secondary metabolites in clove leaves (Syzygium aromaticum L.) in the n-hexane and ethyl acetate fractions. The research methodology includes phytochemical screening of secondary metabolites of the n-hexane and ethyl acetate fractions of clove leaves (Syzygium aromaticum L.) with dye reagents and LC-HRMS analysis. Phytochemical screening of the n-hexane fraction confirmed the presence of steroids, while the ethyl acetate fraction confirmed flavonoids, tannins, and steroids. The results of identification using the LC-HRMS instrument on the N-Hexane and Ethyl Acetate fractions of clove leaves (Syzygium aromaticum L) using LC-HRMS contained phenolic, flavonoid and phenylpropanoid compounds. In the results of the chromatogram in the N-Hexane fraction, Rhamnetin compound was obtained which had an area percent of 0.362% with the highest area of 10954249. Meanwhile, in the results of the ethyl acetate fraction chromatogram, eugenol compounds were obtained with an area percent of 0.37% with the highest area of 33151358.